Multiple-unit franchising and performance outcomes - Bodey, Kelli; Weaven, Scott; Grace, Debra (Journal of Business Economics and Management, 2013)
The economic and social contribution of franchising is widely reported. Although, most studies have examined franchising from the single-unit typology, multiple-unit franchising is found to be a popular and pervasive retailing strategy throughout the world. Despite this, there is a paucity of prior research examining the factors influencing the achievement of the four franchising imperatives. This represents an important gapin the organizational choice literature. Therefore, this study empirically examines the impact of the four franchising imperatives (i.e. unit growth, system uniformity, local responsiveness and system wide adaptation) (Bradach 1995) upon franchise system operational performance across the four key governance structures (i.e. master franchising, area development franchising, area representative franchising and incremental franchising). Based on a sample of 347 Australian franchisors, the findings indicate that there are significant differences in the way in which three of the four imperatives (i.e. unit growth, system uniformity and system-wide adaptation) impact on performance across different governance structures. Practical and managerial implications and future research direction are discussed.